Increasing age as a major determinant of major adverse outcomes in patients with atrial fibrillation: the EURObservational research programme in atrial fibrillation general long-term registry. (25th November 2020) - Boriani, G; Proietti, M; Laroche, C; Piot, O; Lane, D.A; Potpara, T; Maggioni, A.P; Lip, G.Y.H
Abstract: Introduction: Increasing age is a well-known determinant for incident atrial fibrillation (AF) as well as for adverse outcomes. With a progressively ageing population in Europe (and elsewhere), contemporary data are needed to investigate the impact of age in relation to major adverse events in AF patients. Purpose: To evaluate the impact of increasing age on major adverse outcomes in a contemporary European AF cohort. Methods: Patients enrolled in the EORP-AF Long Term General Registry were categorized by age: <65, 65–74, 75–84, and ≥85 years. Any thromboembolic event (TE)/acute coronary syndrome (ACS)/cardiovascular (CV) death, CV death, all-cause mortality were considered as outcomes. Results: Among the 9762 patients included in this analysis, 2946 (30.2%) were <65 years, 3288 (33.7%) were 65–74 years, 2954 (30.3%) were 75–84 years and 574 (5.9%) were ≥85 years. With increasing age categories, there was a progressively higher prevalence of most risk factors and comorbidities. Accordingly, both mean CHA2DS2-VASc and HAS-BLED scores were progressively higher across the age categories (both p<0.0001). At discharge, use of any oral anticoagulant (OAC) drug was lower in patients ≥85 years compared to those aged 65–74 or 75–84 years (83.6% vs. 89.4% and 88.8%, respectively) but significantly higher than in those <65 years (80.2%) [p<0.001]. Rate of all major adverse events progressively increased across the age categories, being higher in those aged ≥85 (all p<0.001). Kaplan-Meier curves showed an increasing cumulative risk across the age groups for all the outcomes (p<0.0001) (Figure 1). A fully adjusted Cox regression analysis demonstrated a progressively increasing association between age categories and the risk of all major adverse outcomes (Table 1). Conclusions: In a large contemporary cohort of European AF patients, increasing age was a major determinant of major adverse outcomes. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Since the start of EORP programme, several companies supported its activities with unrestricted grants.